PENTINGNYA MEMAHAMI PERAN METODOLOGI STUDI ISLAM TERHADAP GENERASI MILENIAL DI ERA DIGITALISASI - Danil, Muhammad (Universitas Muhammadiyah Surakarta, 2020)
The methodology of Islamic studies is said to be of urgency for the current millennial generation. Where the teaching of islam, which are a doctrinal legacy, have been swallowed up by the times along with the development of modern digitalization. Therefore, the aims of this research is to find out more about the importance of Islamic study methodology for the millennial generation. By using a qualitative descriptive method, the author uses a cognitive moral development approach and behavioral psychology which are expected to be able to understand the methodology of Islamic studies to the millennial generation. Millennial generation or often called Gen Y, their interest in Islamic studies is not because of coercion. But their goal in understanding Islam in more detail in the midst of technological sophistication, is because they will make Islam their way of life. Islam should be used as a guideline by the current millennial generation, who have been exposed to the internet since birth so that they do not take wrong steps in the future. To do this, they can get to know Islamic studies further through existing approaches as well as Islamic character education which is then applied in everyday life.